The Role of Economic Concepts of Income in Accounting - Elbadri , Dr. Abdussalam (Dirasat in Economics and Business, 2009)
This paper is devoted to the role of economic income in accounttan cy with emphasis on the economic income in economic theory as well as in accounting. It includes an introduction to well-known concepts of income in economics such as those advanced by Fisher and by Hicks